THE EFFECT OF SHADOWING TECHNIQUE ON STUDENTS’ SPEAKING ABILITY OF EIGHT GRADE AT SMP NEGERI 1 PARIGI - Astriyani, Melly; Miliha, La; Fatmawati, Wa Ode (Universitas Halu Oleo, 2019)
The objective of this study is to find out the effect of shadowing technique on students’ speaking ability. The design of this study is quasi experimental were consist of two classes; experimental class and control class of students’ eight grade students at SMP Negeri 1 Parigi. The researcher applied purposive sampling technique. The instrument of this research was oral test in pre-test and post-test. This study was conducted from March 21st to April 7th, 2018. The instrument used for collecting data were speaking test and the data was analyzed by using SPSS version 16.0. The findings show the students speaking score in experimental class is higher than the students speaking score in control class. It has proved by the comparison of the mean score from both control class and experimental class. The mean score of post-test in control group is 2.52 and the mean score of post-test in experimental group is 3.31. The gain score from post-test in control group to post-test in experimental group is 0.79. Furthermore, the effect size of the study is 0.6 and it indicates there is any significant effect of shadowing technique on students’ speaking ability of eight grade students’ at SMP Negeri 1 Parigi. In short, shadowing technique is recommended to teacher to be use in teaching and learning process as an additional technique in teaching speaking especially to students speaking ability. Keywords: Speaking Ability, Shadowing technique